THE USE OF DIGITAL EDUCATIONAL RESOURCES IN THE FORMATION OF MEDICAL PROFESSIONAL SKILLS - Bakhriddinova Yorkinoy Numanovna (Ecominds Press, 2025)
This paper explores the role of digital educational resources (DERs) in developing professional skills in medical education. It discusses how tools such as virtual simulations, interactive platforms, and multimedia content enhance learning, engagement, and skill development. The integration of English-medium DERs not only improves access to global medical knowledge but also strengthens communication and terminology usage. The paper outlines benefits, classroom applications, and challenges associated with DER implementation, emphasizing the need for a blended, pedagogically sound approach in modern medical training.